Improvement of revised international staging system risk stratification in patients with newly diagnosed multiple myeloma using a high bone marrow plasma cell percentage: a real-world study in China - Sun, Xiaoman; Song, Min; Wang, Pengyu; Zhang, Zhongmei; Dai, Rongqin; Shi, Jie (Frontiers in Oncology, 2025)
Multiple myeloma (MM) is a heterogeneous malignant plasma cell neoplasm. A significant increase in the bone marrow plasma cell percentage (BMPC%) may adversely affect prognosis. However, a high BMPC% has not been clearly defined. The Revised International Staging System (R-ISS) is considered the standard risk stratification model for newly diagnosed MM (NDMM) and is widely used to assess prognosis. However, a significant proportion of patients were categorized as R-ISS stage II due to high heterogeneity within the population, complicating the accurate prediction of prognosis. This study included 208 patients who were diagnosed with NDMM and received standardized treatment between January 2018 and May 2023, and were categorized into low, medium, and high BMPC% groups. The Kaplan-Meier method was utilized to estimate the progression-free survival (PFS) and overall survival (OS). The Cox proportional hazards model was used to estimate the relationship between BMPC% and survival in patients with R-ISS stage II. The results indicated that a high BMPC% significantly negatively affected OS (hazard ratio [HR] = 4.13, p = 0.002), indicating an adverse prognostic factor. Compared with the low and intermediate BMPC% groups, the high BMPC% group exhibited the shortest median survival time (p < 0.001). Additionally, we analyzed the effect of BMPC% on survival rates stratified by R-ISS stage. Within the stage II subgroup, the OS for the BMPC% stratified groups were NA, 50.1 months, and 29.6 months (p = 0.01). We used external validation to confirm the reliability of the results. The results also indicated that a high BMPC% significantly negatively affected OS (p < 0.001). This study demonstrated that including a BMPC% ≥ 50% can enhance the predictive value of the R-ISS for NDMM, particularly in patients with R-ISS stage II.